2023
DOI: 10.2174/1381612829666221212101501
|View full text |Cite
|
Sign up to set email alerts
|

NorA, Tet(K), MepA, and MsrA Efflux Pumps in Staphylococcus aureus, their Inhibitors and 1,8-Naphthyridine Sulfonamides

Abstract: Antibiotic resistance can be characterized, in biochemical terms, as an antibiotic’s inability to reach its bacterial target at a concentration that was previously effective. Microbial resistance to different agents can be intrinsic or acquired. Intrinsic resistance occurs due to inherent functional or structural characteristics of the bacteria, such as antibiotic-inactivating enzymes, nonspecific efflux pumps, and permeability barriers. On the other hand, bacteria can acquire resistance mechanisms via horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 543 publications
0
6
0
Order By: Relevance
“…It has experimentally been observed that the reduction in MIC efflux substrates such as antibiotics and EtBr indicates efflux pump inhibition by a test compound. Therefore, it is reasonable to assume that OEPT contains components that act as inhibitors of NorA, Tet(K), and MepA in S. aureus strains [ 56 , 57 ]. Additionally, the increased fluorescence emission by the strains indicates that the essential oil possibly inhibited the NorA and MepA efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…It has experimentally been observed that the reduction in MIC efflux substrates such as antibiotics and EtBr indicates efflux pump inhibition by a test compound. Therefore, it is reasonable to assume that OEPT contains components that act as inhibitors of NorA, Tet(K), and MepA in S. aureus strains [ 56 , 57 ]. Additionally, the increased fluorescence emission by the strains indicates that the essential oil possibly inhibited the NorA and MepA efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…An important reason for the choice of S. aureus 1199B for study is that its resistance to norfloxacin is known to result from the presence of the Nor A efflux pump [50,68]. Efflux pumps require regulated ion balance to function so that exogeneous substances such as antibacterials can effectively be ejected.…”
Section: Efflux Pump Inhibitionmentioning
confidence: 99%
“…isolates, P. digitatum strain HS-F6 and P. italicum strain YN1 [9,[26][27][28]. Unlike MFS and ABC, MATE superfamily transporters are usually associated with bacterial antibiotic resistance [29], and in contrast, contribute to fungal drug resistance in a few cases [30,31]. Genomics and RNA-seq studies revealed multiple iso-genes encoding MFS and ABC transporters as contributors to developing fungicide resistance.…”
Section: Introductionmentioning
confidence: 99%